A kind of Low-E coated glass and preparation method thereof
By using magnetron sputtering process and heat treatment technology in coated glass, a silver oxide micro-oxide layer is formed, and by optimizing the film layer structure, the problem of uneven distribution of silver layer and difficulty in synchronizing the conductivity and transmittance is solved, efficient improvement of conductivity and transmittance is achieved, and the stability and wear resistance of the film layer are maintained.
Patent Information
- Application Number
- CN202510127968.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-05
AI Technical Summary
In large-scale industrial production, the Ag layer is continuous sputtering, making it difficult to adjust the sputtering gas on each coating product, resulting in uneven distribution of the silver layer, difficulty in synchronizing the electrical conductivity and transmittance, and problems such as oxidation, vulcanization, water stains, oil stains or scratches are prone to occur.
When the magnetically controlled sputtering process is used to increase the oxygen flux of the sputtering gas, preset free oxygen, and diffuse oxygen atoms into the silver layer through heat treatment to form a silver oxide micro-oxide layer. At the same time, the sacrificial layer and protective layer groups are designed to optimize the film layer structure to improve conductivity and transmittance.
The uniform distribution of the silver layer is achieved, the roughness of the silver layer is reduced, the synchronous improvement of conductivity and transmittance is improved, and the design of the sacrificial layer and protective layer is prevented from over-oxidation, and the stability and wear resistance of the film layer are maintained.
Smart Images

Figure CN119569354B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coated glass, and in particular to a Low-E coated glass and a preparation method thereof. Background Art
[0002] LOW-E glass, also known as low-radiation glass, is a film product composed of multiple layers of metal or other compounds coated on the glass surface. Its coating layer has the characteristics of high transmittance of visible light and high reflection of mid- and far-infrared rays, which makes it have excellent heat insulation effect and good light transmittance compared with ordinary glass and traditional architectural coated glass. At the same time, the multi-layer film structure can also improve the electrical conductivity of glass. This transparent conductive film has excellent light transmittance and conductivity, and has great potential in the fields of green energy saving, electromagnetic protection, transparent electrodes, etc. Domestic and foreign research on transparent conductive films is in-depth and extensive. The high conductivity and high energy-saving function of the functional layer Ag layer of the silver-containing transparent conductive film make it the most core technology and key material in the field of green building energy saving to reduce the energy consumption of building curtain walls and improve energy-saving indicators.
[0003] During the research, it was found that appropriate thermal oxidation treatment can change the transmittance and surface resistance of the film layer. There are also literature reports that AgOx can improve the film quality of the Ag layer and promote the increase of carrier concentration and conductivity. However, in the large-scale industrial production process, the Ag layer is sputtered continuously, and it is difficult to adjust the sputtering gas at the beginning or end of the sputtering of the Ag layer of each coated product.
[0004] Generally speaking, high conductivity and high light transmittance are contradictory, and achieving both high light transmittance and high conductivity at the same time is the main problem facing transparent conductive materials. In the subsequent processing, problems such as oxidation, sulfidation, water stains, oil stains or scratches are more likely to occur, which need to be optimized and modified during the film structure design and production process.
[0005] How to obtain a transparent conductive film with a regular structure containing a nanosilver layer, achieve simultaneous improvement in transmittance and conductivity and maintain good stability has become a major problem faced in the development and structural design of transparent conductive film materials. Summary of the invention
[0006] In view of the technical problems existing in the prior art, the present invention aims to provide a Low-E coated glass and a preparation method thereof.
[0007] One of the purposes of the present invention is to provide a method for preparing Low-E coated glass, which adopts a magnetron sputtering process for coating, and when sputtering a transparent conductive oxide layer located at a lower layer relative to a silver layer, increases the oxygen flux of the sputtering gas, so that free oxygen is preset in the transparent conductive oxide layer located at a lower layer relative to the silver layer;
[0008] After coating, heat treatment is performed to diffuse the preset free oxygen into the silver layer to form a silver oxide micro-oxidation layer.
[0009] Preferably, oxygen accounts for 1-5% of the sputtering gas.
[0010] The second object of the present invention is to provide a Low-E coated glass, wherein the Low-E coated glass comprises a glass substrate, a dielectric layer, a functional layer group and a protective layer group;
[0011] On the glass substrate, the dielectric layer is used as the starting layer, and the dielectric layer and the functional layer group are arranged alternately, the total number of the functional layer group is n, the total number of the dielectric layer is n+1, n=1~3, and the outermost layer is the protective layer group;
[0012] The nth functional layer group is located below the n+1th dielectric layer and is farthest from the glass surface compared to other functional layer groups;
[0013] A sacrificial layer is arranged in the nth functional layer group, and the nth functional layer group includes, from bottom to top, a transparent conductive oxide lower layer, a silver layer, a sacrificial layer and a transparent conductive oxide upper layer; other functional layer groups include, from bottom to top, a transparent conductive oxide lower layer, a silver layer and a transparent conductive oxide upper layer.
[0014] The direction from bottom to top refers to the direction from the glass substrate to the protective layer group; the transparent conductive oxide layer below the silver layer refers to the transparent conductive oxide lower layer.
[0015] Preferably, the sacrificial layer is a NiCr layer;
[0016] Preferably, the thickness of the sacrificial layer is 2-4 nm;
[0017] Preferably, the protective layer group includes a ZrOx layer and a graphite layer from bottom to top, and the thickness of the graphite layer is 0.5-2 nm.
[0018] Preferably, the thickness of the silver layer is 8-14 nm.
[0019] Preferably, the thickness of the first dielectric layer and the (n+1)th dielectric layer in the dielectric layer is 30-37 nm, and the thickness of the remaining dielectric layers is 65-68 nm.
[0020] Preferably, the material of the dielectric layer includes one or more of SiNx, SiOx, ITO, TiOx, ZrOx, AlOx, ZnOx, NbOx and AZO.
[0021] Preferably, the material of the transparent conductive oxide lower layer and the transparent conductive oxide upper layer includes one or more of AlOx, ZnOx, NbOx and AZO.
[0022] Beneficial effects of the present invention:
[0023] The present invention adopts magnetron sputtering process for film coating, sputters a transparent conductive oxide located at a relatively lower layer of the metal layer in a mixed gas of oxygen and argon in a preset ratio, and diffuses oxygen atoms of the transparent conductive oxide layer to the silver layer during heat treatment of the composite film, thereby forming an AgOx micro-oxidation layer at the AZO / Ag interface, changing the lattice mismatch rate of AZO and silver, promoting uniform distribution of the silver layer, reducing the roughness of the silver layer, improving conductivity, and achieving simultaneous improvement of high light transmittance and high conductivity.
[0024] Since the micro-oxidation and rearrangement of silver can improve the conductivity and transmittance of the film, once the silver layer is over-oxidized to form too much AgOx, the effective carrier density and the effective thickness of the silver conductive functional layer will be reduced, causing the overall conductivity of the film to deteriorate. During the heat treatment process, the sacrificial layer is continuously oxidized to prevent oxygen atoms from diffusing from the upper interface of the transparent conductive oxide to the silver layer, preventing the silver layer from being over-oxidized.
[0025] The ZrOx film and graphite film improve the hydrophobicity and corrosion potential of the film layer, and improve the wear resistance. After high-temperature heat treatment, the graphite will be oxidized and removed, and the water stains, oil stains, micro scratches and other defects on the graphite surface will disappear with the removal of the graphite layer. After high-temperature heat treatment, the surface ZrOx and SiNx layers are more dense, showing higher scratch resistance and fouling resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0027] Figure 1 This is a schematic diagram of the structure of the Low-E coated glass according to Example 11 of the present invention;
[0028] L1 is the first dielectric layer, L2 is the first transparent oxide lower layer, L3 is the first Ag layer, L4 is the first transparent oxide upper layer, L5 is the second dielectric layer, L6 is the second transparent oxide lower layer, L7 is the second Ag layer, L8 is the second transparent oxide upper layer, L9 is the third dielectric layer, L10 is the third transparent oxide lower layer, L11 is the third Ag layer, L12 is a sacrificial layer, L13 is the third transparent oxide upper layer, L14 is the fourth dielectric layer, L15 is a ZrOx layer, and L16 is a graphite layer;
[0029] L2, L3 and L4 are the first functional layer group, L6, L7 and L8 are the second functional layer group, and L10, L11, L12 and L13 are the third functional layer group. DETAILED DESCRIPTION
[0030] According to the first aspect of the present invention, a method for preparing Low-E coated glass is provided, wherein the coating is performed by magnetron sputtering, and when sputtering a transparent conductive oxide layer located relatively below the silver layer, the oxygen flux of the sputtering gas is increased, so that free oxygen is preset in the transparent conductive oxide layer located relatively below the silver layer;
[0031] After coating, heat treatment is performed to diffuse the preset free oxygen into the silver layer to form a silver oxide micro-oxidation layer.
[0032] In the present invention, the oxygen flux of the sputtering gas is increased, so that the oxygen overflow in the transparent conductive oxide layer can be suppressed, and a small amount of free oxygen or dissolved oxygen is pre-set in the transparent conductive oxide layer. The oxygen atoms of the transparent conductive oxide layer diffuse into the silver layer during the subsequent heat treatment of the composite film, so that an AgOx micro-oxidation layer is formed at the AZO / Ag interface. For example, when the transparent conductive oxide is AZO, a structural bridge of Ag-AgOx-ZnO is established between the silver layer and the transparent conductive oxide layer, so that the lattice mismatch rate of AZO and silver is changed, the uniform distribution of the silver layer is promoted, the roughness of the silver layer is reduced, and the conductivity is improved.
[0033] In a preferred embodiment of the present invention, oxygen accounts for 1-5% of the sputtering gas.
[0034] In the present invention, the conductivity and transmittance of the film layer can be improved due to the micro-oxidation and rearrangement of silver, but once the silver layer is over-oxidized to form too much AgOx, the effective carrier density and the effective thickness of the silver conductive functional layer will be reduced, resulting in the deterioration of the overall conductivity of the film layer. For example, oxygen is 1%, 2%, 3%, 4% or 5% of the sputtering gas.
[0035] According to a second aspect of the present invention, a Low-E coated glass is provided, wherein the Low-E coated glass comprises a glass substrate, a dielectric layer, a functional layer group and a protective layer group;
[0036] On the glass substrate, the dielectric layer is used as the starting layer, and the dielectric layer and the functional layer group are arranged alternately, the total number of the functional layer group is n, the total number of the dielectric layer is n+1, n=1~3, and the outermost layer is the protective layer group;
[0037] The nth functional layer group is located below the n+1th dielectric layer and is farthest from the glass surface compared to other functional layer groups;
[0038] A sacrificial layer is provided in the nth functional layer group, and the nth functional layer group includes, from bottom to top, a transparent conductive oxide lower layer, a silver layer, a sacrificial layer, and a transparent conductive oxide upper layer; and other functional layer groups include, from bottom to top, a transparent conductive oxide lower layer, a silver layer, and a transparent conductive oxide upper layer;
[0039] In the present invention, n is 1, 2 or 3, for example.
[0040] In the present invention, the method for preparing Low-E coated glass specifically includes:
[0041] The glass substrate is first cleaned and dried, and the preset sputtering gas argon and / or reactive gas oxygen or nitrogen are filled into the coating chamber, and then the film is coated in the coating sequence through the magnetron sputtering process; when sputtering the transparent conductive oxide located at the lower layer of the silver layer, the sputtering gas in the coating chamber is a mixed gas of oxygen and argon, and oxygen accounts for 1-5% of the sputtering gas.
[0042] After the film is plated, it is moved into a heat treatment furnace. The film is heated from room temperature to 400-500°C at a rate of 50-60°C / minute, and then heated to 600-800°C at a rate of 120-150°C / minute, and then kept warm for 20-80 seconds, and then cooled naturally or with weak wind or strong blowing to room temperature.
[0043] Herein, the direction from bottom to top refers to the direction from the glass substrate to the protective layer group.
[0044] In a preferred embodiment of the present invention, the sacrificial layer is a NiCr layer with a thickness of 2-4 nm.
[0045] In the present invention, the thickness of the NiCr layer will have a great influence on the transmittance of the film layer. Therefore, it is necessary to maintain the minimum thickness of the NiCr layer in the film layer structure design, so that the film layer can just complete the NiCr oxidation during the heat treatment process, and the silver layer will not be oxidized and damaged, so that the transmittance and conductivity of the coated glass can reach the optimal value. When the NiCr layer thickness is greater than 4nm, NiCr will remain after the heat treatment is completed, and the transmittance of the film layer is too low. When it is less than 2nm, NiCr will be consumed in advance during the high temperature process, and the Ag layer will be excessively oxidized and damaged, and the overall conductivity of the film layer will deteriorate.
[0046] In a preferred embodiment of the present invention, the protective layer includes a ZrOx layer and a graphite layer in sequence, and the thickness of the graphite layer is 0.5-2 nm.
[0047] In the present invention, after high-temperature heat treatment, the graphite will be oxidized and removed, and defects such as water stains, oil stains, micro scratches on the graphite surface will disappear with the removal of the graphite layer. After high-temperature heat treatment, the surface ZrOx and SiNx layers are denser, showing higher scratch resistance and fouling resistance.
[0048] In a preferred embodiment of the present invention, the thickness of the graphite layer is 0.5-2 nm.
[0049] In the present invention, when the thickness of the top graphite layer is less than 0.5nm, the graphite layer has incomplete coverage, and the hydrophobic and anti-scratch effects are poor. When the thickness of the graphite layer is greater than 2nm, graphite residues will remain after subsequent high-temperature heat treatment, and stains will not be completely removed. In addition, a thicker graphite layer will reduce the overall transmittance of the Low-E film.
[0050] In a preferred embodiment of the present invention, the thickness of the silver layer is 8-14 nm.
[0051] In a preferred embodiment of the present invention, the thickness of the first dielectric layer and the (n+1)th dielectric layer in the dielectric layer is 30-37 nm, and the thickness of the remaining dielectric layers is 65-68 nm.
[0052] In a preferred embodiment of the present invention, the material of the dielectric layer includes one or more of SiNx, SiOx, ITO, TiOx, ZrOx, AlOx, ZnOx, NbOx and AZO.
[0053] In a preferred embodiment of the present invention, the material of the transparent conductive oxide lower layer and the transparent conductive oxide upper layer includes one or more of AlOx, ZnOx, NbOx and AZO.
[0054] Example 1
[0055] The present embodiment includes Low-E coated glass and a preparation method thereof. The structure of the Low-E coated glass is: 6G / SiNx / AZO / Ag / NiCr / AZO / SiNx / ZrOx / graphite. In this structure, the functional layer group is AZO / Ag / NiCr / AZO, that is, the transparent conductive oxide lower layer and the transparent conductive oxide upper layer are AZO with a thickness of 10nm, the metal layer is Ag with a thickness of 12nm, the sacrificial layer is NiCr with a thickness of 3nm, the dielectric layer is SiNx, the first dielectric layer has a thickness of 30nm, the second dielectric layer has a thickness of 32nm, the protective layer is ZrOx / graphite, and the graphite layer has a thickness of 1nm; n=1, that is, the total number of functional layers is 1, and the total number of dielectric layers is 2.
[0056] The preparation method comprises the following steps:
[0057] First, the glass substrate is cleaned and dried, and the coating chamber is filled with a preset sputtering gas argon and / or reactive gas oxygen or nitrogen, and then the coating is performed according to the coating sequence by magnetron sputtering. The sputtering process parameters are shown in Table 1;
[0058] After the film is plated, it is moved into a heat treatment furnace. The film is heated from room temperature to 400-500°C at a rate of 50-60°C / minute, and then raised to 650°C at a rate of 120-150°C / minute, and then kept warm for 20-80 seconds, and cooled naturally or by blowing to room temperature to obtain Low-E coated glass.
[0059] Table 1 Magnetron sputtering process parameters
[0060]
[0061] Example 2
[0062] The process gas ratio during sputtering of the AZO layer is Ar:O2=99:1, and the remaining steps and parameters are the same as those in Example 1.
[0063] Example 3
[0064] The process gas ratio when sputtering the AZO layer is Ar:O2=95:5, and the remaining steps and parameters are the same as those in Example 1.
[0065] Example 4
[0066] The thickness of the NiCr layer is 4 nm, the thickness of the graphite layer is 0.5 nm, and the remaining steps and parameters are the same as those in Example 1.
[0067] Example 5
[0068] The thickness of the NiCr layer is 2 nm, the thickness of the graphite layer is 2 nm, and the remaining steps and parameters are the same as those in Example 1.
[0069] Example 6
[0070] The Ag layer is 10 nm, Ar:O2=98:2, the NiCr thickness is 3 nm, the protective layer is ZrOx / graphite, the graphite layer thickness is 1 nm, and the remaining steps and parameters are the same as in Example 1.
[0071] Example 7
[0072] Take n=2, that is, the total number of functional layers is 2, and the total number of dielectric layers is 3; the Low-E coated glass structure is: 6G / SiNx / AZO / Ag / AZO / SiNx / AZO / Ag / NiCr / AZO / SiNx / ZrOx / graphite, the thickness of the first dielectric layer is 32nm, the thickness of the second dielectric layer is 68nm, the thickness of the third dielectric layer is 29nm, the thickness of the first Ag layer is 10nm, the thickness of the second Ag layer is 12nm, the process gas ratio when sputtering the AZO layer is Ar:O2=98:2, NiCr is 2.6 nm, and the thickness of the graphite layer is 0.8nm. The remaining steps and parameters are the same as those in Example 1.
[0073] Example 8
[0074] The thickness of the first Ag layer is 10 nm, the thickness of the second Ag layer is 12 nm, the process gas ratio when sputtering the AZO layer is Ar:O2=98:2, the NiCr is 3.0 nm, and the thickness of the graphite layer is 0.5 nm. The remaining steps and parameters are the same as those in Example 1.
[0075] Example 9
[0076] The thickness of the first Ag layer is 10 nm, the thickness of the second Ag layer is 12 nm, the process gas ratio when sputtering the AZO layer is Ar:O2=96:4, the NiCr is 2.0 nm, and the thickness of the graphite layer is 2 nm. The remaining steps and parameters are the same as those in Example 1.
[0077] Example 10
[0078] The thickness of the first Ag layer is 10 nm, the thickness of the second Ag layer is 12 nm, the process gas ratio when sputtering the AZO layer is Ar:O2=99:1, the NiCr is 2.6 nm, and the thickness of the graphite layer is 0.8 nm. The remaining steps and parameters are the same as those in Example 1.
[0079] Embodiment 11
[0080] Take n=3, that is, the total number of functional layers is 3, and the total number of dielectric layers is 4; the Low-E coated glass structures are: 6G / SiNx(I) 33 nm / AZO / Ag(I) 10 nm / AZO / SiNx(II) 63 nm / AZO / Ag(II) 12 nm / AZO / SiNx(III) 67 nm / AZO / Ag(III) 14 nm / AZO / SiNx(IV) 18 nm / ZrOx 11 nm / graphite, the thickness of the first dielectric layer is 33 nm, the thickness of the second dielectric layer is 59 nm, the thickness of the third dielectric layer is 64 nm, and the thickness of the fourth dielectric layer is 11 nm. nm, the thickness of the first Ag layer is 10 nm, the thickness of the second Ag layer is 12 nm, the thickness of the third Ag layer is 14 nm, the process gas ratio when sputtering the AZO layer is Ar:O2=98:2, the NiCr is 2.6 nm, and the thickness of the graphite layer is 0.8 nm. The remaining steps and parameters are the same as those in Example 1.
[0081] Example 12
[0082] The process gas ratio during sputtering of the AZO layer is Ar:O2=98:2, the NiCr is 2 nm, and the graphite layer thickness is 2 nm. The remaining steps and parameters are the same as those in Example 11.
[0083] Embodiment 13
[0084] The process gas ratio during sputtering of the AZO layer is Ar:O2=98:2, the NiCr is 3 nm, and the graphite layer thickness is 0.5 nm. The remaining steps and parameters are the same as those in Example 11.
[0085] Embodiment 14
[0086] The process gas ratio during sputtering of the AZO layer is Ar:O2=96:4, the NiCr is 4 nm, and the graphite layer thickness is 0.5 nm. The remaining steps and parameters are the same as those in Example 11.
[0087] Comparative Example 1
[0088] n=1, that is, the total number of functional layers is 1, and the total number of dielectric layers is 2. The metal layer is Ag with a thickness of 12 nm, the dielectric layer is SiNx, the first dielectric layer has a thickness of 30 nm, the second dielectric layer has a thickness of 32 nm, the process gas during sputtering of the AZO layer is Ar99.9% or more, no NiCr and graphite layers are provided, no heat treatment is performed, and the rest is the same as in Example 1.
[0089] Comparative Example 2
[0090] n=1, that is, the total number of functional layers is 1, and the total number of dielectric layers is 2. The metal layer is Ag with a thickness of 10 nm, the dielectric layer is SiNx, the first dielectric layer has a thickness of 30 nm, the second dielectric layer has a thickness of 32 nm, the process gas during sputtering of the AZO layer is Ar99.9% or more, no NiCr and graphite layers are provided, no heat treatment is performed, and the rest is the same as in Example 1.
[0091] Comparative Example 3
[0092] The metal layer is Ag with a thickness of 12 nm. The process gas during sputtering of the AZO layer is Ar 99.9% or more. NiCr and graphite layers are not provided. Heat treatment is performed. The rest is the same as in Example 1.
[0093] Comparative Example 4
[0094] The metal layer is Ag with a thickness of 10 nm. The process gas during sputtering of the AZO layer is Ar 99.9% or more. No NiCr and graphite layer is provided. Heat treatment is performed. The rest is the same as in Example 1.
[0095] Comparative Example 5
[0096] The metal layer is Ag with a thickness of 12 nm, the process gas during sputtering of the AZO layer is Ar:O2=98:2, the NiCr layer is 2 nm thick, the graphite layer is 1 nm thick, no heat treatment is performed, and the rest is the same as in Example 1.
[0097] Comparative Example 6
[0098] The metal layer is Ag with a thickness of 12 nm, the process gas during sputtering of the AZO layer is Ar:O2=98:2, the NiCr layer is 5 nm thick, the graphite layer is 1 nm thick, and heat treatment is performed. The rest is the same as in Example 1.
[0099] Comparative Example 7
[0100] The metal layer is Ag with a thickness of 12 nm, the process gas during sputtering of the AZO layer is Ar:O2=98:2, the NiCr layer is 3 nm thick, the graphite layer is 5 nm thick, and heat treatment is performed. The rest is the same as in Example 1.
[0101] Comparative Example 8
[0102] The metal layer is Ag with a thickness of 12 nm, the process gas during sputtering of the AZO layer is Ar:O2=93:7, the NiCr layer is 3 nm thick, the graphite layer is 1 nm thick, and heat treatment is performed. The rest is the same as in Example 1.
[0103] Comparative Example 9
[0104] Take n=2, that is, the total number of functional layers is 2, and the total number of dielectric layers is 3; the Low-E coated glass structure is: 6G / SiNx / AZO / Ag / AZO / SiNx / AZO / Ag / NiCr / AZO / SiNx / ZrOx / graphite, the thickness of the first dielectric layer is 32nm, the thickness of the second dielectric layer is 68nm, the thickness of the third dielectric layer is 29nm, the thickness of the first Ag layer is 10nm, the thickness of the second Ag layer is 12nm, the process gas ratio when sputtering the AZO layer is Ar content of more than 99%, the NiCr layer is 0 nm, the graphite layer is 0nm, and no heat treatment is performed. The remaining steps and parameters are the same as those in Example 7.
[0105] Comparative Example 10
[0106] The process gas ratio during sputtering of the AZO layer is an Ar content of more than 99%, the NiCr layer is 0 nm, the graphite layer thickness is 0 nm, and heat treatment is performed. The remaining steps and parameters are the same as those in Example 7.
[0107] Comparative Example 11
[0108] The process gas ratio during sputtering of the AZO layer is Ar:O2=94:6, the NiCr layer is 6 nm, the graphite layer is 5 nm thick, and heat treatment is performed. The remaining steps and parameters are the same as those in Example 7.
[0109] Comparative Example 12
[0110] Take n=3, that is, the total number of functional layers is 3, and the total number of dielectric layers is 4; the Low-E coated glass structures are: 6G / SiNx(I) 33 nm / AZO / Ag(I) 10 nm / AZO / SiNx(II) 63 nm / AZO / Ag(II) 12 nm / AZO / SiNx(III) 67 nm / AZO / Ag(III) 14 nm / AZO / SiNx(IV) 18 nm / ZrOx 11 nm / graphite, the thickness of the first dielectric layer is 33 nm, the thickness of the second dielectric layer is 59 nm, the thickness of the third dielectric layer is 64 nm, and the thickness of the fourth dielectric layer is 11 nm. nm, the thickness of the first Ag layer is 10 nm, the thickness of the second Ag layer is 12 nm, the thickness of the third Ag layer is 14 nm, the process gas ratio when sputtering the AZO layer is Ar greater than 99%, NiCr is 0 nm, the thickness of the graphite layer is 0 nm, and no heat treatment is performed. The remaining steps and parameters are the same as those in Example 11.
[0111] Comparative Example 13
[0112] The process gas ratio during sputtering of the AZO layer is Ar greater than 99%, NiCr is 0 nm, the graphite layer thickness is 0 nm, and heat treatment is performed. The remaining steps and parameters are the same as those in Example 11.
[0113] Comparative Example 14
[0114] The process gas ratio during sputtering of the AZO layer is Ar:O2=96:4, the NiCr is 3.0 nm, the graphite layer thickness is 5 nm, and heat treatment is performed. The remaining steps and parameters are the same as those in Example 11.
[0115] Performance Testing
[0116] Optical performance test and calculation method:
[0117] The optical performance test of transparent conductive film adopts infrared / visible light / ultraviolet spectrophotometer, model PE Lambda950 Perkin Elmer. With D65 as light source, the full spectrum test from 300 nm to 2500 nm is carried out to obtain three sets of spectral data, including transmission, film surface reflection, and glass surface reflection.
[0118] According to GB / T 2680-2021, the visible light transmittance, reflectance, etc. are calculated by comprehensively considering the photopic spectral efficiency and the relative spectral power distribution of the light source. The calculation method is shown in the following formula (GB / T 2680-2021).
[0119]
[0120]
[0121] in:
[0122] T —— visible light transmittance, %
[0123] R —— visible light reflectance, %
[0124] —— Visible light spectrum transmittance, %
[0125] —— Visible light spectrum reflectance, %
[0126] —— Relative spectral power distribution of standard illuminant D65, see GB / T 2680-2021;
[0127] —— Luminous efficiency of photopic vision spectrum, see GB / T 2680-2021;
[0128] —— Wavelength interval, which is chosen to be 5 nm.
[0129] Conductivity test method:
[0130] The surface resistance of the transparent conductive film is tested using an inductor coil type surface resistance meter (NAGY, SRM-12TH, Germany). During the measurement, the surface resistance meter will generate a changing magnetic field, and the conductor of the conductive product under test placed in the magnetic field will generate induced eddy currents. Measuring the size of the induced eddy current can calculate the surface resistance of the material, which is a non-destructive measurement method.
[0131] Comprehensive photoelectric performance evaluation:
[0132] Since high conductivity and high transmittance are mutually restrictive and mutually exclusive, if one property is pursued alone, the other property must be abandoned. In the study of transparent conductive films, the Hake index (Figure-of-Merit, also known as quality factor) is used to evaluate the photoelectric properties of the film, which comprehensively evaluates the transmittance and surface resistance. The calculation formula is:
[0133]
[0134] Where: T —— visible light transmittance, %;
[0135] Rsh——film surface resistance, Ω / sq;
[0136] Φ——Film Hake index, mΩ -1 .
[0137] Table 2 Performance test results
[0138]
Claims
1. A method for preparing Low-E coated glass, characterized in that: The film is deposited by a magnetron sputtering process. When sputtering a transparent conductive oxide layer located relatively below the silver layer, the oxygen flux of the sputtering gas is increased so that free oxygen is preset in the transparent conductive oxide layer located relatively below the silver layer. After coating, heat treatment is performed to diffuse the preset free oxygen into the silver layer, forming a silver oxide micro-oxidation layer, promoting uniform distribution of the silver layer and reducing the roughness of the silver layer; The oxygen gas accounts for 1-5% of the sputtering gas.
2. A Low-E coated glass obtained by the method for preparing Low-E coated glass according to claim 1, characterized in that: The Low-E coated glass comprises a glass substrate, a dielectric layer, a functional layer group and a protective layer group; On the glass substrate, the dielectric layer is used as the starting layer, and the dielectric layer and the functional layer group are arranged alternately, the total number of the functional layer group is n, the total number of the dielectric layer is n+1, n=1~3, and the outermost layer is the protective layer group; The nth functional layer group is located below the n+1th dielectric layer and is farthest from the glass surface compared to other functional layer groups; A sacrificial layer is provided in the nth functional layer group, and the nth functional layer group includes, from bottom to top, a transparent conductive oxide lower layer, a silver layer, a sacrificial layer, and a transparent conductive oxide upper layer; and other functional layer groups include, from bottom to top, a transparent conductive oxide lower layer, a silver layer, and a transparent conductive oxide upper layer; The sacrificial layer is a NiCr layer; The thickness of the NiCr layer is 2-4 nm.
3. The Low-E coated glass according to claim 2, characterized in that: The protective layer group includes a ZrOx layer and a graphite layer from bottom to top, and the thickness of the graphite layer is 0.5-2nm.
4. The Low-E coated glass according to claim 2, characterized in that: The thickness of the silver layer is 8-14 nm.
5. The Low-E coated glass according to claim 2, characterized in that: The thickness of the first dielectric layer and the (n+1)th dielectric layer in the dielectric layer is 30-37 nm, and the thickness of the remaining dielectric layers is 65-68 nm.
6. The Low-E coated glass according to claim 2, characterized in that: The material of the dielectric layer includes one or more of SiNx, SiOx, ITO, TiOx, ZrOx, AlOx, ZnOx, NbOx and AZO.
7. The Low-E coated glass according to claim 2, characterized in that: The material of the transparent conductive oxide lower layer and the transparent conductive oxide upper layer includes one or more of AlOx, ZnOx, NbOx and AZO.
Citation Information
Patent Citations
Glazing coated with thin layers
CN101980985A
Three-silver light-adjusting glass
CN103144380A
Low-emissivity coated laminated glass containing crystalline silver layer as well as preparation method and application of low-emissivity coated laminated glass
CN114702252A